Identity and Community in the Iron Age - Potrebica, Hrvoje (2011)
European Iron Age studies over the years demonstrate that there are significant and fundamental differences in understanding as well as spatial and conceptual definition of different cultural entities, such as cultural complexes, cultural groups, ethnic groups, or communities. That seriously affects any attempt to study character, content and meaning of various interactions between specific groups of people. Introduction of all sorts of different inclusive or exclusive criteria for such entities, regardless of their relation to different features of material culture, or more abstract concepts such as burial ritual, instead of bringing more clarity and introducing universally accepted tools, succeeded only in creating even larger confusion in creation of general picture of the Iron Age cultural dynamics. Obviously, it is time to change the scope of our analysis and take step backwards from “general picture” and large theoretical models, to smaller, actual groups of people and their actual interactions in time/space framework. Another necessary change related to identity issues is change of perspective. Most of identity labels in the Iron Age are product of “others” and not of actual communities to which they refer. There is also question of changing identity and how does it reflect structure modification of any community over any period of time. Specific problem arises from different definitions of communities and their identity markers, based on historical, archaeological, anthropological, ethnographic sources. The Southern Pannonia, with its intensive and complex cultural dynamics from the Late Bronze Age to the historical times of Roman conquest, provide excellent arena for study of all sorts identity issues related to different communities and their interaction. This paper will try to use some of these examples as case studies for general discussion on identity and community in the Iron Age Europe.
Projekt MZOS
ENG